2011
DOI: 10.1371/journal.pone.0020429
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Physiological Analysis of Iron Biofortification in Maize Kernels

Abstract: BackgroundMaize is a major cereal crop widely consumed in developing countries, which have a high prevalence of iron (Fe) deficiency anemia. The major cause of Fe deficiency in these countries is inadequate intake of bioavailable Fe, where poverty is a major factor. Therefore, biofortification of maize by increasing Fe concentration and or bioavailability has great potential to alleviate this deficiency. Maize is also a model system for genomic research and thus allows the opportunity for gene discovery. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 46 publications
3
80
1
Order By: Relevance
“…Moreover, recombinant hybrid line formed from crossing of two distantly related lines may help in mapping and identifying of quantitative and single trait loci like in Medicago [80] and wheat [81]. Different crops such as maize and rice line with novel traits have been screened on the basis of Fe uptake and its biobioavailability analysis [82].…”
Section: Non-transgenic Iron Biofortification Methodsmentioning
confidence: 99%
“…Moreover, recombinant hybrid line formed from crossing of two distantly related lines may help in mapping and identifying of quantitative and single trait loci like in Medicago [80] and wheat [81]. Different crops such as maize and rice line with novel traits have been screened on the basis of Fe uptake and its biobioavailability analysis [82].…”
Section: Non-transgenic Iron Biofortification Methodsmentioning
confidence: 99%
“…Several QTL studies have been conducted in maize for grain mineral concentration (Garcia-Oliveira et al 2009;Zhou et al 2010;Lung'aho et al 2011;Qin et al 2012;Šimic et al 2012;Baxter et al 2013Baxter et al , 2014. Stable or consistent QTL across different environments could only be identified in some of these above studies.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, environment affects both the traits simultaneously in the same direction or sometimes in different directions (Yücel et al, 2009). Several studies have reported significant positive correlation between Fe and Zn contents in maize and other crops (Baxter et al, 2013;Chakraborti et al, 2009;Lungaho et al, 2011;Baloch et al, 2014). This could be possibly due to linkage between the genes affecting the accumulations or pleotropic effects of the genes governing the accumulation of micronutrients and the existence of one or more common genetic-physiological mechanisms involved in mineral absorption or uptake by the root system, translocation and redistribution within the plant tissues, remobilization to the grain, or accumulation in the developing grain (Çakmak, 2008;Peleg et al, 2008;Chatvaz et al, 2010).…”
Section: Discussionmentioning
confidence: 98%